X+9-4x=-3x-3

Simple and best practice solution for X+9-4x=-3x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+9-4x=-3x-3 equation:


Simplifying
X + 9 + -4x = -3x + -3

Reorder the terms:
9 + X + -4x = -3x + -3

Reorder the terms:
9 + X + -4x = -3 + -3x

Solving
9 + X + -4x = -3 + -3x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + X + -9 + -4x = -3 + -9 + -3x

Reorder the terms:
9 + -9 + X + -4x = -3 + -9 + -3x

Combine like terms: 9 + -9 = 0
0 + X + -4x = -3 + -9 + -3x
X + -4x = -3 + -9 + -3x

Combine like terms: -3 + -9 = -12
X + -4x = -12 + -3x

Add '4x' to each side of the equation.
X + -4x + 4x = -12 + -3x + 4x

Combine like terms: -4x + 4x = 0
X + 0 = -12 + -3x + 4x
X = -12 + -3x + 4x

Combine like terms: -3x + 4x = 1x
X = -12 + 1x

Simplifying
X = -12 + 1x

See similar equations:

| g=2(2)+1 | | 4x+7-2x=-4 | | x+0.2x=53 | | 1/2-400x=5000 | | 4/5x=-141/35 | | g=2(0)+1 | | 10x-131=5x-6 | | 12/y=30/9 | | g=2(-1)+1 | | 7x+6=66 | | 6x-7+2x+8=x+5-2x+12 | | g=2(-2)+1 | | -3x+4=5x-8 | | (6x-1)/2=9 | | (x+12)(x-1)=2(x-6)-20 | | 6x+3*(-3)=9 | | 6x-1/2=9 | | -7.8x+2.4x=40 | | -4+4X=-16+13 | | 6*2+3y=9 | | 2x-5+4x+10=21 | | 24x^3+8x^2=100x^2+-28x | | -2(-4-3x)=-28 | | 6x+1=12-2x | | 7*log(3x)+3log(5x)=15 | | 20+9b=38 | | 7x-11+9=180 | | 18+3x=24+2x | | 3y+45=90 | | 1/2x-4=7/3 | | 12x+375=639 | | 0.6x+120=0.68x-448 |

Equations solver categories